The Edible Mushroom Pleurotus spp.: II. Medicinal Values - Helmi Johari Masri, Helmi Johari Masri; Parisa Maftoun, Parisa Maftoun; Abd Malek, Roslinda; Zineddine Boumehira, Ali; Pareek, Avnish; Zulaiha Hanapi, Siti; Mei Ling, Ong; El Enshasy, Hesham (International Journal of Biotechnology for Wellness Industries, 2017)
Mushrooms health benefit was recognized in the Orient from several thousand years ago as globally consumption and has third largest commercially production. The genus Pleurotus (oyster mushroom) is an organoleptic fast growing fungus which belongs to basidiomycota group. Although 70 species is discovered until now for this genus, but only few of them are available in market such as Pleurotus florida, P. sajor-caju and P. ostreatus. They have been used in human diet throughout the world due to their rich nutrients such as protein, fiber carbohydrate, minerals, vitamins and lipid. It should be noted that low amount calories, Sodium, fat and cholesterol is reported in this genus. Many pharmaceutical companies in the Far East and China are viewing the medicinal mushrooms as a rich source of innovative biomedical molecules. These molecules can be extracted from different part of oyster mushroom such as fruiting body, mycelia and culture broth. Mainly they are biopolymers including polysaccharides, proteins and nucleic acids as they are more variable to carry biological information. The medicinal properties of Pleurotus spp studied by several authors, as a result antitumor, immunomodulating, antiviral, antibacterial, antigenotoxic, antioxidant, anti-inflammatory, hypocholesterolamic, antihypertensive, antiinociceptive, anti-hyperglycaemic, anti-platelet-aggregating, antihepatoma, anti poliferative and antiatherosclerotic. In this chapter, biodivertsity of genus Pleurotus will be discussed regarding nutritional and bioactive compounds. Furthermore the prospective of oyster mushroom for therapeutic application and concept will be highlighted.